Application of Biological Nitrogen Fixation Cyanobacteria To Paddy Plant Cultivated Under Deep-Water Culture System - Dian Hendrayanti; Iman Rusmana; Dwi Andreas Santosa; Hamim Hamim (UIN Sunan Gunung Djati Bandung, 2020)
The Biological Nitrogen Fixing (BNF) cyanobacteria can reduce atmospheric nitrogen into ammonium. This ability makes BNF cyanobacteria a potential eco-friendly N-source for soil-planted pad-dy. Apart from a few success stories of BNF cyanobacteria applica-tion in the rice field, its role as an ammonium producer is still an open question. There is also a possibility that indeed cyanobacteria biomass which provides nitrogen through the biological decomposing process. This study aimed to analyze the influence of three strains BNF cyanobacteria on paddy grown in the Deep-Water Culture (DWC) hydroponic system. Yoshida Nutrient Solution was used as a growth medium with the application of 0, 45.7, and 91.4 gL-1 of ammonium nitrate (NH4NO3) with five replications. The result showed that inter-action between cyanobacteria and nitrogen significantly influenced the total nitrogen of paddy plant, but not the paddy plant height, the num-ber of tillers, and biomass. Cyanobacterial filaments were found most-ly attached to the paddy root rather than floated in the DWC system. Paddy treated with cyanobacteria had more lateral root than control. The result suggested that cyanobacteria support paddy growth indi-rectly through nitrogen deposition in plant tissue and root development.